STRATEGIES IN EXPRESSING THANKING IN ENGLISH REALIZED BY INDONESIAN LEARNERS - - Dalilan (Universitas Katolik Indonesia Atma Jaya, 2012)
This study describes the gratitude strategies realized by Indonesian EFL learners in responding to different situations. Data were collected from 17 undergraduate students of English Department of Education Faculty of Atmajaya Catholic University Jakarta by using (O’Keeffe et.al, 2011) Discourse Completion Tasks. This study revealed that the gratitude strategies employed by the participants of this study ranged from simple, brief thankings to lenghty, complex thankings. All participants produced mixed speect act sets of thanking in the following conditions: a) social status (between a vice-president and a newly hired personnel, b) indebtedness (because of money loan and meal treat), and c) breaking promise. On the other hand, in informal contexts, such as between friends and the setting of public area, the participants tended to use simple or brief thanking.